(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article delves into the intricate analysis of pragmatic and stylistic features present in archaic words within English and Uzbek proverbs. By examining the usage of archaic vocabulary in these culturally significant linguistic expressions, the study aims to shed light on the nuanced interplay between language evolution, pragmatic communication, and stylistic expression in proverbial discourse. Through a comparative analysis of English and Uzbek proverbs containing archaic terms, the research uncovers the unique semantic, sociocultural, and historical dimensions embedded within these linguistic artefacts. Furthermore, the article explores how the retention and adaptation of archaic words in proverbs serve as potent vehicles for preserving cultural heritage, conveying moral truths, and fostering intergenerational communication. By unraveling the pragmatic and stylistic intricacies of archaic vocabulary in proverbial language, this study contributes to a deeper understanding of the dynamic interconnections between language, culture, and communication practices across diverse linguistic traditions.